Chronic alcohol use affects therapeutic steady state plasma drug concentrations of stavudine, lamivudine and nevirapine in HIV-infected patients during 9 months follow up period: WHO AUDIT tool application - Bbosa, Godfrey S.; Kyegombe, David B.; Anokbonggo, William W.; Ntale, Muhammad; Musoke, David; Odda, John; Lubega, Aloysius; Ogwal-Okeng, Jasper (International Journal of Basic & Clinical Pharmacology, 2013)
Chronic alcohol consumption is a common problem among the HIV-infected patients on HAART. The study determined the effect of chronic alcohol use on steady state plasma drug concentrations of stavudine (d4T), lamivudine (3TC) and nevirapine (NVP) in HIV-infected patients during the 9 months follow up period. It also determined whether there were some patients with undetectable plasma drug concentrations in their plasma during the follow up. A case control using repeated measures design with serial measurements model, where plasma drug concentrations were measured at 3 month intervals was used. Chronic alcohol-use using WHO AUDIT tool was used to screen patients. A total of 41 patients (21 alcohol group and 20 control group) were followed up for 9 months with blood sampling done at 3 month intervals. The Shimadzu Class-VPTM HPLC Chromatography data system version 6.1 equipment with UV detector was used to measure the plasma drug concentrations. Data was analyzed using SAS 2003 version 9.1 statistical package with repeated measures fixed the model and means were compared using the student t-test. The mean steady state plasma concentration of both d4T and 3TC in chronic alcohol use group were lower than in the control group all throughout the 9 months period of follow-up. The mean steady state plasma drug concentrations of NVP were higher in the alcohol group at 0 and 3 months and lower in the 6 and 9 months as compared to the control group. The mean total plasma NVP concentration was higher in the chronic alcohol group as compared to the control group and the difference was statistically significant (p≤0.05). However some patients had undetectable plasma drug concentrations despite of having ≥ 95 % adherence rate. Chronic alcohol use by the HIV-infected patients lowers the steady state plasma drug concentrations of d4T, 3TC and NVP in patients.
Keywords: Chronic alcohol use; Therapeutic steady state plasma drug concentrations; HIV